Cyclin D1 expression in acral melanoma : a case control study in Sarawak - Zainal Abidin, Ibrahim; M Zulkarnaen, A Narihan; Dk Norlida, A Ojep; Ashley Edward Roy, Soosay; Kok Long, Pan (Malaysian J Pathol, 2012)
Acral melanoma has been reported to have distinctive clinical presentation and ethnic distribution compared to other histological types of malignant melanoma. Acral melanoma also exhibits distinctive focused gene amplifications, including cyclin D1 overexpression. We reviewed archived histological material of malignant melanoma in the Sarawak General Hospital from year 2004 to 2010. 43 tumours, comprising 28 acral melanoma and 15 non-acral melanoma, had sufficient material to be included in the study. The majority (36%) of acral melanoma tumours occurred in the heel. The tumours were analyzed for cyclin D1 expression by immunohistochemistry. 68% of acral melanoma were cyclin D1 positive compared to a positivity of 33% in non-acral tumours. This difference was statistically significant (p < 0.05). This finding may improve the histological diagnosis of acral melanoma and detection of positive resection margins.